Molecular Mechanisms and Therapeutic Potential of Gabapentin with a Focus on Topical Formulations to Treat Ocular Surface Diseases - Dario Rusciano (MDPI AG, 2024)
Gabapentin (GBP) was originally developed as a potential agonist for Gamma-Amino-Butyric-Acid (GABA) receptors, aiming to inhibit the activation of pain-signaling neurons. Contrary to initial expectations, it does not bind to GABA receptors. Instead, it exhibits several distinct pharmacological activities, including: (1) binding to the alpha-2-delta protein subunit of voltage-gated calcium channels in the central nervous system, thereby blocking the excitatory influx of calcium; (2) reducing the expression and phosphorylation of CaMKII via modulation of ERK1/2 phosphorylation; (3) inhibiting glutamate release and interfering with the activation of NMDA receptors; (4) enhancing GABA synthesis; (5) increasing cell-surface expression of δGABA_A receptors, contributing to its antinociceptive, anticonvulsant, and anxiolytic-like effects. Additionally, GBP displays (6) inhibition of NF-kB activation and subsequent production of inflammatory cytokines, and (7) stimulation of the purinergic adenosine A1 receptor, which supports its anti-inflammatory and wound-healing properties. Initially approved for treating seizures and postherpetic neuralgia, GBP is now broadly used for various conditions, including psychiatric disorders, acute and chronic neuropathic pain, and sleep disturbances. Recently, as an eye drop formulation, it has also been explored as a therapeutic option for ocular surface discomfort in conditions such as dry eye, neurotrophic keratitis, corneal ulcers, and neuropathic ocular pain. This review aims to summarize the evidence supporting the molecular effects of GBP, with a special emphasis on its applications in ocular surface diseases.